Numerical Path Integral Approach to Quantum Dynamics and Stationary Quantum States (Communications in Computational Physics, 2018)
Applicability of Feynman path integral approach to numerical simulationsof quantum dynamics of an electron in real time domain is examined. Coherent quantumdynamics is demonstrated with one dimensional test cases (quantum dot models)and performance of the Trotter kernel as compared with the exact kernels is tested.Also, a novel approach for finding the ground state and other stationary sates is presented.This is based on the incoherent propagation in real time. For both approachesthe Monte Carlo grid and sampling are tested and compared with regular grids andsampling. We asses the numerical prerequisites for all of the above.